2018
DOI: 10.12965/jer.1836152.076
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-acetylcysteine supplementation on cellular damage and oxidative stress indicators in volleyball athletes

Abstract: The purpose of this study was to evaluate the effects of N-acetylcysteine (NAC) supplementation on cellular damage and oxidative stress indicators in volleyball athletes. Twenty male volleyball athletes at national level performed a physical training session and were divided into 2 groups, which for 7 days took the placebo substance or NAC. After 7 days the athletes repeated the same training session. In both sessions, blood samples were collected 30 min before and immediately after the training session to mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Selçuk et al [26] concluded that a ten-day acute training program resulted in changes in AST, ALT, CK and some biochemical parameters of tennis players. In another study conducted by de Moraes et al (2018), it was reported that training and Nacetylcysteine (NAC) supplement caused changes in ALT, AST, LDH, ALP, CK and some biochemical parameters, indicators of cell damage and oxidative stress in volleyball players, and N-acetylcysteine (NAC) provided with training would decrease oxidant effect [27]. Akbulut [28] expressed that eight weeks of resistance exercises had important effects on liver enzymes and body composition of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Selçuk et al [26] concluded that a ten-day acute training program resulted in changes in AST, ALT, CK and some biochemical parameters of tennis players. In another study conducted by de Moraes et al (2018), it was reported that training and Nacetylcysteine (NAC) supplement caused changes in ALT, AST, LDH, ALP, CK and some biochemical parameters, indicators of cell damage and oxidative stress in volleyball players, and N-acetylcysteine (NAC) provided with training would decrease oxidant effect [27]. Akbulut [28] expressed that eight weeks of resistance exercises had important effects on liver enzymes and body composition of participants.…”
Section: Discussionmentioning
confidence: 99%
“…NAC supplementation was administered to several specific groups of athletes, including cyclists [100,101], triathletes [73], rowers [99], and volleyball players [98] to determine their role in redox related changes. Researchers also evaluated the possible effects of NAC on exercise-induced oxidative stress and adaptive mechanisms in healthy untrained men [68][69][70]72,74,[80][81][82][83][84], recreationally trained men [13,74,[85][86][87][88][89][90][91][92], and endurance-trained men [17,[94][95][96].…”
Section: Possible Role Of N-acetylcysteine During the Regulation Of Oxidative Stress Response Of Mitochondria To Exercisementioning
confidence: 99%
“…Researchers also evaluated the possible effects of NAC on exercise-induced oxidative stress and adaptive mechanisms in healthy untrained men [68][69][70]72,74,[80][81][82][83][84], recreationally trained men [13,74,[85][86][87][88][89][90][91][92], and endurance-trained men [17,[94][95][96]. Most studies primarily focused on the effects of NAC supplementation on GSH and GSH-related biomarkers in muscle [13,80,91,94] and plasma [68][69][70]74,82,83,85,90,91,98,99,101], and total or reduced NAC in muscle [17,101] and plasma [17,74,88]. However, it is challenging to comment on the relationship between NAC and glutathione availability, as studies differ in dose [17,83,<...>…”
Section: Possible Role Of N-acetylcysteine During the Regulation Of Oxidative Stress Response Of Mitochondria To Exercisementioning
confidence: 99%
See 2 more Smart Citations